Surgery for Sleep Disordered Breathing - Hörmann, Karl; Verse, Thomas (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The treatment of sleep disordered breathing has been enriched by the development of various new and largely surgical techniques. The question of which treatment best suits each individual patient has become a highly sophisticated decision. Among others, the most important factors for selecting the most appropriate treatment modality are the cruelty of the disease, the pathology found within the upper airway, and the sites of obstruction. Therefore, the second edition of this book focuses on both the surgical treatment modalities and the current concepts for treatment decisions. For each procedure, current data (including data for the entirety of 2007) were reanalyzed according to the principles of evidence-based medicine, and are presented in well-arranged tables. Indications, techniques, complications, and specific follow-up treatments in the realm of sleep medicine have been compiled in the form of a primer. New chapters concerning radiofrequency-uvulopalatoplasty and combined soft palate procedures were added. Both authors run prominent otolaryngological sleep laboratories, and perform approximately 1,500 surgical sleep medicine procedures per year. The complete surgical and sleep medicine expertise of the authors, as well as the experience of numerous international courses on sleep surgery, have been incorporated into this volume, making it an indispensable textbook for sleep medicine surgeons.